Phthalimide Derivatives with Bioactivity against Plasmodium falciparum: Synthesis, Evaluation, and Computational Studies Involving bc1 Cytochrome Inhibition - Okada-Junior, Celso Yassuo; Monteiro, Gustavo Claro; Aguiar, Anna Caroline Campos; Batista, Victor Sousa [UNESP]; De Souza, Juliana Oliveira; Souza, Guilherme Eduardo; Bueno, Renata Vieira; Oliva, Glaucius [UNESP]; Nascimento-Júnior, Nailton M. [UNESP]; Guido, Rafael Victorio Carvalho; Bolzani, Vanderlan Silva (American Chemical Society (ACS), 2018)
We describe herein the design and synthesis of N-phenyl phthalimide derivatives with inhibitory activities against Plasmodium falciparum (sensitive and resistant strains) in the low micromolar range and noticeable selectivity indices against human cells. The best inhibitor, 4-amino-2-(4-methoxyphenyl)isoindoline-1,3-dione (10), showed a slow-acting mechanism similar to that of atovaquone. Enzymatic assay indicated that 10 inhibited P. falciparum cytochrome bc1 complex. Molecular docking studies suggested the binding mode of the best hit to Qo site of the cytochrome bc1 complex. Our findings suggest that 10 is a promising candidate for hit-to-lead development.